Beryllium global erosion and deposition at JET-ILW simulated with ERO2.0. (January 2019) - Romazanov, J.; Brezinsek, S.; Borodin, D.; Groth, M.; Wiesen, S.; Kirschner, A.; Huber, A.; Widdowson, A.; Airila, M.; Eksaeva, A.; Borodkina, I.; Linsmeier, Ch.; et al.
Highlights: 3D simulations of Be erosion at JET-ILW in limiter and divertor configuration. Effective erosion yields agree within a factor of 2 with spectroscopic measurements. Limiter configuration: over one third of Be erosion at IW is due to self-sputtering. Divertor configuration: significant Be deposition on top of the inner divertor. Cross-field drifts enhance Be migration into the divertor due to SOL flows. Abstract: The recently developed Monte-Carlo code ERO2.0 is applied to the modelling of limited and diverted discharges at JET with the ITER-like wall (ILW). The global beryllium (Be) erosion and deposition is simulated and compared to experimental results from passive spectroscopy. For the limiter configuration, it is demonstrated that Be self-sputtering is an important contributor (at least 35%) to the Be erosion. Taking this contribution into account, the ERO2.0 modelling confirms previous evidence that high deuterium (D) surface concentrations of up to  ∼ 50% atomic fraction provide a reasonable estimate of Be erosion in plasma-wetted areas. For the divertor configuration, it is shown that drifts can have a high impact on the scrape-off layer plasma flows, which in turn affect global Be transport by entrainment and lead to increased migration into the inner divertor. The modelling of the effective erosion yield for different operational phases (ohmic, L- and H-mode) agrees with experimental values within a factor of two, and confirms that the effective erosion yield decreases with increasing heating power and confinement.